Teaching Peace: Nonviolence and the Liberal Arts - Weaver, Denny J.; Biesecker-Mast, Gerald (Rowman & Littlefield Publishers, 2003)
This book opens a new frontier in understanding nonviolence. Discussions of peace and nonviolence usually focus on either moral theory or practical dimensions of applying nonviolence in conflict situations. Teaching Peace carries the discussion of nonviolence beyond ethics and into the rest of the academic curriculum. This book isn't just for religion or philosophy teachers—it is for all educators. Teaching Peace begins with a discussion rooted in Christian theology, where nonviolence is so central and important. But it is clear that there are other paths to nonviolence, and that one certainly doesn't have to be a Christian to practice nonviolence. The pieces that follow, therefore, show how a nonviolent perspective impacts disciplines across the curriculum—from acting, to biology, to mathematics, to psychology.